The interactive support of cognitive reserve and semantic knowledge in proper name retrieval. Issue 1 (2nd January 2023) - Montemurro, Sonia; Montefinese, Maria; Serena, Martina; Pucci, Veronica; Mondini, Sara; Semenza, Carlo
ABSTRACT: Cognitive reserve (CR) refers to acquired experience that modulates resistance to physiological aging or brain damage. A relatively neglected issue is whether or not CR affects cognitive abilities equally. One relevant component of CR seems to be the richness of connections in semantic knowledge. We examined, in N = 66 healthy older adults, the potential influence of CR and semantic knowledge on the ability to retrieve proper names and common nouns. These two name categories have different semantic organisations, whereby proper names are characterised by a weaker semantic link to the information they refer to. Controlling for age, CR and semantic knowledge were linearly and positively associated with common noun retrieval. On the other hand, CR assisted proper name retrieval in older adults with a weaker semantic profile, while semantic knowledge assisted proper name retrieval in older adults with lower CR. This study contributes to define the cognitive underpinnings of CR.